Palliative Care at Home: Alternative Routes for Pharmaceutical Administration - Martins de Brito, Sérgio (2022)
Palliative care is intended to improve the patients and patient’s families life quality in cases of serious and/or advanced, incurable or progressive diseases. Symptomatic management (pharmacological and non-pharmacological) is one of its areas of action, since its lack of control negatively influences the quality of life of the patient and his family. The oral route is the preferred therapeutic route in palliative care, however, there are situations in which its use is not possible. Thus, it becomes important to have alternative therapeutic routes to fulfill the objective of keeping the patient comfortable at home. The aim of this work is to present the advantages and disadvantages of the most used alternative routes and their possible therapeutic options for the different symptoms.